Glucose syrups : technology and applications - Hull, Peter , 1934- (Chichester, U.K. ; Ames, Iowa : Wiley-Blackwell, 2010)
Intends to bring together the relevant information on the manufacture and use of glucose syrups. This book is suitable for those involved in the processing and buying of these syrups, and for scientists involved in the manufacture of food products in which the syrups are ingredients.
1. History of glucose syrups -- 2. Fructose containing syrups -- 3. Glucose syrup manufacture -- 4. Explanation of glucose syrup specifications -- 5. SApplication properties of glucose syrups -- 6. Syrup applications: an overview -- 7. Trehalose -- 8. Sugar alcohols: an overview -- 9. Glucose syrups in baking and biscuit products -- 10. Glucose syrups in brewing -- 11. Glucose syrups in confectionery -- 12. Glucose syrups in fermentations: an overview -- 13. Glucose syrups in ice cream and similar products -- 14. Glucose syrups in jam -- 15. Glucose syrups in tomato products and other types of dressing and sauces -- 16. Glucose syrups in soft drinks -- 17. Glucose syrups in health and sports drinks -- 18. Carbohydrate metabolism and caloric values -- 19. Caramel - the colouring
Includes bibliographical references (p. 357-360) and index
Keywords: Corn syrup; Glucose